Corrigendum to “On the computation of the multidimensional Mittag–Leffler function” (Commun. Nonlinear Sci. Numer. Simulat. (2017) 53 (278–287) (S1007570417301594) (10.1016/j.cnsns.2017.05.007)) - Ortigueira, Manuel D. (2019)
In the paper entitled “On the computation of the multidimensional Mittag–Leffler function” there is an error that originates some misleading nomenclature and results. The phrase in Section 2, page 2, three lines after equation (4), should be written as follows: “As the Laplace transform (LT) of [Formula-presented] to obtain the LT of the M-MLF, c α,β (t), from: [Formula-presented] This means that the computations with β ≠ 1 represent the inverse Laplace transform of C α,β (s) instead of that of the Mittag–Leffler function.